BLOOD ANALYSIS OF DIFFERENT BREEDS OF CARPSIAN FISH - Khurramova S. G.; Kupalova S.B.; Kurbanov F. E. (Bright Mind Publishing, 2025)
During the experiment, it was found that the morphological, physiological and hematological parameters of the blood of fish kept in bioecological conditions differ depending on the morphophysiological characteristics of the fish organism in the conditions of storage and the hydrochemistry of the water.
Keywords: Erythrocyte, 1012/l, Hemocrit, Hemoglobin content in erythrocytes, pg, Average erythrocyte size, μm, Leukocyte x1012/l, Extensive technology, Intensive technology, Artificial pond, Hemoglobin in pond conditions, Limited water body